Vehicles for change? Public universities, development plans, and the post-carbon transition in the Gulf states - Esmat Zaidan; Cesar Wazen; Mohammad Al-Saidi (Research in Globalization)
Gulf countries have initiated ambitious national development policies toward economic diversification and implementing global paradigms for sustainable development. These policies are largely oriented towards knowledge-based economies (KBE) through innovations and entrepreneurship. This paper examines the evolving role of higher Education Institutions (HEIs) in translating national policies toward global competitiveness and entrepreneurship. Specifically, the study asks: Are public universities in rentier states drivers of development or instruments of state-led transformation? Using the case of a large national university in an Arab Gulf state, this paper analyses the role, reforms, and self-perception of Qatar University within the development frameworks in Qatar. Using qualitative research methods, the paper emphasizes the contributions of public universities in the Gulf in localizing globalization-induced paradigms related to entrepreneurial education, sustainable development, and the KBE. By highlighting the unique challenges of the GCC region, the paper provides a multifaceted understanding of how universities in the Gulf region operate at the intersection of top-down mandates and bottom-up adaptation. The paper provides a multifaceted understanding of how universities in the Gulf region operate at the intersection of top-down mandates and bottom-up adaptation. It advances academic knowledge regarding the relevance of context and local experiences for implementing global expectations from national HEIs. Largely, these universities are driven by national-level expectations. However, these expectations have created more space for community engagement and for adopting a more progressive societal agenda – particularly regarding sustainable development. Drawing broader implications from the QU case study, the paper suggests policy measures towards more deliberative and participatory strategies for advancing the contributions of HEIs to local development in the Gulf region.